EFEKTIFITAS PENARIKAN ROYALTI BAGI PELAKU USAHA KARAOKE BERDASARKAN UNDANG-UNDANG NOMOR 28 TAHUN 2014 TENTANG HAK CIPTA - Duwi Aprianti (Faculty of Law, Mahasaraswati University, Denpasar, 2020)
Withdrawal Royalties are the utilization of the economic rights of a work related to the receipt by the creator or the copyright holder. Copyright is a creation created by the creator in a tangible form by not reducing restrictions in accordance with the provisions of legislation. Copyright applies in all areas of life one of which is the art of music. Songs that have been registered must get Royalties if they are to be used for commercial purposes, the only other who often violates is a commercial karaoke business in royalty payments. The method used in this study is the empirical law whose purpose gives a description of the provisions in the effort to withdraw royalties for commercial business Karaok